Effectiveness of Piper betle leaf infusion as a palpebral skin antiseptic - Amalia, Husnun; Sitompul, Ratna; Hutauruk, Johan; Andrianjah, Andrianjah; Mun’im, Abdul (Faculty of Medicine, Trisakti University, 2009)
The goal of an antiseptic is to eliminate or greatly reduce the number of microorganisms in the surgical field at the time of the surgery. The objective of this study was to verify the effectiveness of 20% Piper betle leaf infusion as an antiseptic solution in pre-surgery cataract patients. A clinical trial with partner-matching design was conducted on 31 pairs of eyelids. From each pair of eyelids, one eyelid was asigned to the Piper betle infusion group and the opposite one to the povidone-iodine group. The microorganisms were collected by swab from the patient’s palpebral skin, inoculated on nutrient agar, and incubated at 37oC for 20 hours. The antiseptic effectiveness was measured by counting the microbial colonies before and after administration of the antiseptic solutions. This study demonstrates that the mean colony counts after application of 20% Piper betle leaf infusion showed a significant reduction of 27-100% compared with those before administration (p=0.001). Mean colony counts after 10% povidone-iodine administration showed a significant reduction of 88-100% compared with the mean counts before the solution was applied (p=0.000). The 20% Piper betle infusion has an antiseptic potential. Nevertheless, the 10% povidone-iodine solution has more effective antiseptic capability.